Chronic disease risks and use of a smartphone application during a physical activity and dietary intervention in Australian truck drivers. (29th December 2015) - Gilson, Nicholas D.; Pavey, Toby G.; Vandelanotte, Corneel; Duncan, Mitch J.; Gomersall, Sjaan R.; Trost, Stewart G.; Brown, Wendy J.
Abstract: Objective : This study examined chronic disease risks and the use of a smartphone activity tracking application during an intervention in Australian truck drivers (April‐October 2014). Methods : Forty‐four men (mean age=47.5 [SD 9.8] years) completed baseline health measures, and were subsequently offered access to a free wrist‐worn activity tracker and smartphone application (Jawbone UP) to monitor step counts and dietary choices during a 20‐week intervention. Chronic disease risks were evaluated against guidelines; weekly step count and dietary logs registered by drivers in the application were analysed to evaluate use of the Jawbone UP. Results : Chronic disease risks were high (e.g. 97% high waist circumference [≥94 cm]). Eighteen drivers (41%) did not start the intervention; smartphone technical barriers were the main reason for drop out. Across 20‐weeks, drivers who used the Jawbone UP logged step counts for an average of 6 [SD 1] days/week; mean step counts remained consistent across the intervention (weeks 1–4=8, 743[SD 2, 867] steps/day; weeks 17–20=8, 994[SD 3, 478] steps/day). The median number of dietary logs significantly decreased from start (17 [IQR 38] logs/weeks) to end of the intervention (0 [IQR 23] logs/week; p <0.01); the median proportion of healthy diet choices relative to total diet choices logged increased across the intervention (weeks 1–4=38[IQR 21]%; weeks 17–20=58[IQR 18]%). Conclusions : Step counts were more successfully monitored than dietary choices in those drivers who used the Jawbone UP. Implications : Smartphone technology facilitated active living and healthy dietary choices, but also prohibited intervention engagement in a number of these high‐risk Australian truck drivers.